Hydraena lotti sp. nov., a new member of the “Haenydra” lineage from the Peloponnese (Greece), with additional records of Hydraena species in the region (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2013)
Hydraena lotti sp. nov. (Coleoptera, Hydraenidae) is described from the southern Peloponnese, Greece; the 92nd known member of the “Haenydra” lineage. The new species belongs to the H. emarginata complex, being closest morphologi-cally to Hydraena pelops Jäch, 1995, from the south and east of the Taygetos range, H. pangaei Jäch, 1992, endemic to Mount Pangaeon in northeastern Greece, and H. samnitica Fiori, 1904, from central Italy. Characters on which the species can be distinguished are discussed; male genitalia and female elytral apices being particularly diagnostic. The ecology of H. lotti is described in the context of other members of the genus in the region. To date, the new species has only been found in small headwater streams at altitudes above 1,000 m in the northwest of the Taygetos range, where it can, however, be locally frequent. The opportunity is taken to provide an updated checklist of Peloponnese “Haenydra”, together with new distributional records of selected Hydraena species, including H. arachthi Ferro & Jäch, 2000, which is reported from the peninsula for the first time.